2009
DOI: 10.1371/journal.pone.0006609
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Forkhead Box M1 Transcription Factor from Respiratory Epithelial Cells Inhibits Pulmonary Tumorigenesis

Abstract: The Forkhead Box m1 (Foxm1) protein is induced in a majority of human non-small cell lung cancers and its expression is associated with poor prognosis. However, specific requirements for the Foxm1 in each cell type of the cancer lesion remain unknown. The present study provides the first genetic evidence that the Foxm1 expression in respiratory epithelial cells is essential for lung tumorigenesis. Using transgenic mice, we demonstrated that conditional deletion of Foxm1 from lung epithelial cells (epFoxm1−/− m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 36 publications
3
63
0
Order By: Relevance
“…Consistent with this is the finding that positive regulators of checkpoint recovery in G2 are commonly overexpressed in cancer and associated with poor prognosis (Bulavin et al, 2002;Cholewa et al, 2013;Li et al, 2002;Wang et al, 2008;Wierstra, 2013). Conversely, tumorigenesis is impaired in their absence (Bulavin et al, 2004;Wang et al, 2009), and several regulators of G2 checkpoint recovery are under (pre)clinical evaluation (Gilmartin et al, 2014;Gumireddy et al, 2005;Stadler et al, 2014). Understanding the mechanisms underlying cellular fate will allow us to devise new therapeutic strategies to sensitise cancer cells to DNA-damaging agents currently used in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this is the finding that positive regulators of checkpoint recovery in G2 are commonly overexpressed in cancer and associated with poor prognosis (Bulavin et al, 2002;Cholewa et al, 2013;Li et al, 2002;Wang et al, 2008;Wierstra, 2013). Conversely, tumorigenesis is impaired in their absence (Bulavin et al, 2004;Wang et al, 2009), and several regulators of G2 checkpoint recovery are under (pre)clinical evaluation (Gilmartin et al, 2014;Gumireddy et al, 2005;Stadler et al, 2014). Understanding the mechanisms underlying cellular fate will allow us to devise new therapeutic strategies to sensitise cancer cells to DNA-damaging agents currently used in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 inactivation in cycling cells caused delays in DNA replication and mitosis, and altered expression of cell cycle regulatory genes (20)(21)(22)(23). Consistent with an important role of FOXM1 in cell cycle progression, FOXM1 induced proliferation of tumor cells during development of lung, liver, brain, and prostate cancers (21,(24)(25)(26)(27). Likewise, FOXM1 accelerated cellular proliferation during acute lung and liver injuries (28,29).…”
mentioning
confidence: 80%
“…Lungs were inflated, fixed in 4% paraformaldehyde, and embedded in paraffin blocks. Five-m sections were stained with hematoxylin and eosin (H&E) or Alcian blue or used for immunohistochemistry as described previously (26,31,43). The following antibodies were used for immunostaining: FOXM1 (1:1,000, K-19, sc500; Santa Cruz Biotechnology), Cre recombinase (1:15,000, 69050-3; Novagen), Clara cell-secreted protein (CCSP; 1:2,000, WRAB-CCSP; Seven Hill Bioreagents), Ki-67 (1:500, clone Tec-3; Dako), PH3 (1:500, sc8656r; Santa Cruz Biotechnology), FOXA2 (1:4,000, WRAB-FoxA2; Seven Hills Bioreagents); FOXA3 (1:200, sc5361; Santa Cruz Biotechnology), ␤-tubulin (1:100, MU178-UC, BioGenex), SPDEF (1:2,000; generated in the lab of J.…”
Section: Mouse Strains Generation Of a Foxm1mentioning
confidence: 99%
“…Recent research has validated the critical role of FOXM1 protein in tumorgenesis. Wang [20] showed that FOXM1 is associated with poor prognosis of non-small cell lung cancer (NSCLC). Furthermore, a striking reduction in the number and size of lung tumors was found following the deletion of FOXM1 from lung epithelial cells prior to tumor initiation in transgenic mice, which resulted primarily from a signi cant decrease in TOPO-2α, a direct target of FOXM1.…”
Section: Discussionmentioning
confidence: 99%